Inhibition of K-BALB murine tumours using Semliki Forest virus and its derived factor - Smyth, James William Peter (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2005)
The induction of cytopathic effects in tumour cells, often by apoptosis, is the primary goal of most non-surgical cancer therapies. Cancer gene therapy represents a variety of potentially therapeutic strategies involving the introduction of new genetic information into cells with the aim of abrogating tumourigenicity or eliciting therapeutic effects. A large proportion of cancer gene therapy research is devoted to immunotherapy, which involves the induction or potentiation of host antitumour immune responses. Antigens associated with tumourigenesis have been identified and exploited in this field, but given the unstable nature of tum our cell phenotype and antigen expression, these strategies may be of limited value. Rather than restricting therapy to a specific antigen, the expression of Semliki Forest virus (SFV) antigens (predominantly E2) is employed in this study with the aim of inducing host immune responses against infected tum our cells.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin